An inverse technique for excitation design in nerve fascicle activation: a theoretical study - Abeyratne, Udantha R. (2013)
Position selective stimulation of nerves is an important problem in FES systems, but no systematic method exists to determine the spatio-temporal excitation current profile. In this paper, we provide a theoretical background towards solving this problem. The efficacy of the technique is investigated through Monte Carlo experiments based on simplified computer models of a nerve.